Conocimiento y prácticas de autocuidado para prevención del pie diabético en adultos con diabetes mellitus - Arevalo Vargas, Simitt Herminia (2024)
The objective of the research was to determine the relationship that exists between knowledge and self-care practices for the prevention of Diabetic Foot in adults with Diabetes Mellitus. The quantitative method and descriptive correlational design were used. The sample was 70 people with Diabetes Mellitus. The survey technique was used and the instruments used were a knowledge questionnaire on diabetic foot prevention and a questionnaire on self-care practices in the prevention of diabetic foot. The results obtained were: 58.6% were between 46 and 65 years old, 51.4% were women, 64.3% had a secondary education degree, 48.6% were housewives, 80% They came from Iquitos, 31.4% had diabetic foot, 30% had a mild degree of diabetic foot. Regarding knowledge of diabetic foot self-care, 75.7% had a low level, in terms of diabetic foot self-care practice, 54.3% demonstrated inadequate practices. By correlating both variables, a (r=-0.351**; r=0.000**, Sig. < 0.01) was obtained. Therefore, the study concludes that there is a highly significant statistical relationship between knowledge and self-care practices to prevent diabetic foot in people treated at the Loreto 2022 Regional Hospital.